Speak Out, Call In Public Speaking as Advocacy - Mapes, Meggie; Open Textbook Library (Open Textbook Library, 2019)
Speak Out, Call In: Public Speaking as Advocacy is a contemporary, interdisciplinary public speaking textbook that fuses rhetoric, critical/cultural studies, and performance to offer an up-to-date resource for students. With a focus on advocacy, this textbook invites students to consider public speaking as a political, purposeful form of information-sharing.
Part I. Advocacy and Audiences -- 1. Public Speaking As Advocacy -- 2. Centering Audiences -- Part II. Arguments and Information -- 3. Selecting and Formulating Arguments -- 4. Researching Arguments -- 5. Crafting Arguments -- 6. Organizing and Outlining -- Part III. Aesthetics and Delivery -- 7. Creating an Aesthetic Experience -- 8. Verbal Delivery -- 9. Nonverbal Delivery -- 10. Presentation Aids -- 11. Rehearsing Your Presentation -- Part IV. Approaches -- 12. Informative Speaking -- 13. Persuasive Speaking -- 14. Online Public Speaking -- 15. Ceremonial Speaking
In English.
Description based on online resource
Keywords: Sociology -- Textbooks